1998
DOI: 10.1016/s0022-5223(98)70362-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel charcoal-induced model of obliterative bronchiolitis–like lesions: Implications of chronic nonspecific airway inflammation in the development of posttransplantation obliterative bronchiolitis

Abstract: Transtracheal injection of activated charcoal into native lungs results in slowly progressive airway injury and inflammation leading to obliterative airway lesions. Inadequate immunosuppression primarily results in chronic vascular rejection but not obliterative bronchiolitis. Underimmunosuppressed allografts subjected to nonspecific airway inflammation develop obliterative airway lesions that are more prominent than in native lungs. This suggests that a cofactor to chronic rejection is likely necessary for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…6 Orthotopic transplantation of the left lung in the rat is an established model to study re-implantation responses and acute rejection. The Brown Norway (BN)¡Lewis (LEW) [7][8][9][10][11][12] and the Fischer 344 (F344)¡Wistar Kyoto (WKY) [13][14][15][16][17] rat strain combinations are commonly used to study chronic changes after lung transplantation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Orthotopic transplantation of the left lung in the rat is an established model to study re-implantation responses and acute rejection. The Brown Norway (BN)¡Lewis (LEW) [7][8][9][10][11][12] and the Fischer 344 (F344)¡Wistar Kyoto (WKY) [13][14][15][16][17] rat strain combinations are commonly used to study chronic changes after lung transplantation.…”
mentioning
confidence: 99%
“…Mild BO can develop 6 months after transplantation. [7][8][9][10] However, this does not happen in all allografts. Uncontrolled factors, such as infections or aspiration of bedding material, might be involved in the pathogenesis of BO in this model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary changes after prolonged installation of charcoal included airway injury and inflammation and led to the development of bronchiolitis obliterans [13].…”
Section: Discussionmentioning
confidence: 99%
“…An experimental animal study (3) found, at 2-4 weeks, randomly dispersed AC particles in the lumen and submucosa of bronchioles and alveolar ducts; AC-laden bronchioles showed evidence of moderate nonspecific inflammation and epithelial injury, and there was vascular and interstitial edema. At 12-20 weeks, there was epithelial sloughing and replacement by cuboidal cells in the AC-laden bronchioles; in the submucosa, there was granulation tissue; progressive intraluminal infiltration by inflammatory cells, fibroblasts, and fibrotic tissue resulted in varying degrees of bronchiolar obstruction; there were diffuse areas of atelectasis and alveolar thickening in the parenchyma; and AC-free sites were normal.…”
Section: To the Editormentioning
confidence: 99%